2012
DOI: 10.1258/ebm.2012.012140
|View full text |Cite
|
Sign up to set email alerts
|

p53 antagonizes the unfolded protein response and inhibits ground glass hepatocyte development during endoplasmic reticulum stress

Abstract: The unfolded protein response (UPR) is triggered during stress of the endoplasmic reticulum (ER) and facilitates tissue homeostasis. Considering the role of p53 tumor suppressor gene in the interpretation of stress-inducing stimuli, in this study, we explored whether p53 modulates UPR. We found that p53 ablation resulted in a profound sensitivity to tunicamycin that was associated with liver dysfunction, ground glass hepatocyte (GGH) development and nuclear atypia/dysplasia. Binding immunoglobulin protein (BiP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
23
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 35 publications
4
23
0
1
Order By: Relevance
“…ATM-defi cient cells undergo hyperactivation of IRE1 when exposed to ionizing radiation ( 119 ), and both p53-defi cient cells and ATM-defi cient cells develop spontaneous alterations in ER proteostasis (119)(120)(121). Cross-talk between the UPR and p53 has been reported in many studies (see examples in refs.…”
Section: Er Stress and Dna Damage/repairmentioning
confidence: 99%
“…ATM-defi cient cells undergo hyperactivation of IRE1 when exposed to ionizing radiation ( 119 ), and both p53-defi cient cells and ATM-defi cient cells develop spontaneous alterations in ER proteostasis (119)(120)(121). Cross-talk between the UPR and p53 has been reported in many studies (see examples in refs.…”
Section: Er Stress and Dna Damage/repairmentioning
confidence: 99%
“…30,35,36 A sound difference between WT and Tm7sf2 KO mice has been detected in p53 expression. While in WT liver p53 shows the typical expression with a peak at 48 h that declines over the following hours, in Tm7sf2 KO mice p53 is intensely and constantly upregulated from 36 until 60 h after PH.…”
Section: Discussionmentioning
confidence: 99%
“…Given the role of the tumor suppressor p53 in stress sensing and in ER stress, 30 as well as in cell cycle gatekeeping through its target gene p21, we decided to explore whether p53 and p21 expression was different in Tm7sf2 WT and KO mice, and whether such a change could justify the data observed and be responsible for the impaired liver regeneration. We observed that in WT mice, a significant peak of p53 protein expression occurred at 48 h and declined at 72 h after PH, whereas in Tm7sf2 KO mice p53 expression was increased starting at 24 h and remained constantly high until 60 h after PH (Fig.…”
Section: Increased Er Stress Response During Liver Regeneration In Tmmentioning
confidence: 99%
“…Tumor suppressor p53 is an antagonizer of the UPR [157], an oscillator itself [158,159], and a regulator of PER2 expression [160]. In p53-deficient mice, submitted to chronic ER stress by tunicamycin (an ER-resident glycosylase), there was a more pronounced UPR (i.e.…”
Section: Crosstalk Between the Upr With Central And Peripheral Oscillmentioning
confidence: 99%
“…In p53-deficient mice, submitted to chronic ER stress by tunicamycin (an ER-resident glycosylase), there was a more pronounced UPR (i.e. induction of GRP78/Bip and GRP94) than in control, and in addition, the alternative splicing of XBP1 was more efficient in cells that did not express p53, pointing to an antagonizing role of p53 on the UPR [157].…”
Section: Crosstalk Between the Upr With Central And Peripheral Oscillmentioning
confidence: 99%